Rendering of ‘La’ala’ & ‘Asaa’ in the Holy Quran: A Semantic Study of Two Translations - M.Jawad, Najat (Al-Adab Journal, 2023)
The object of the study is to look at the English (TT) translation of لعل la’ala and عسى ‘asaa in Arabic Text (ST) of the Holy Quran. They have the same meaning with little differences. Their renderings are investigated and analyzed semantically according to contextual and cohesive meaning of certain texts, i.e. the aayas (verses). The question is: do the translators (al-Hilali &Khan and Irving) succeed in rendering the meanings of the two items from Arabic (source text) into English (target text)? Are there differences between the two translations, or the two items? The study is drawn out that the translators have relatively succeeded in rendering l’ala and ‘asaa. However, it is shown that Arabic (SL) is semantically more precise than English, and the latter has limited expressions compared to the much meanings of the Quranic expressions. Moreover, the two translations are not different in rendering them though Irving’s is more adequate than al-Hilali &Khan’s.